The effect of lactose on the human body - Tolibova Munisa Jurabek qizi; Bazarova Rushana Ilxomovna; Madjidova Inoyat Xafizovna; Asrorova Parvina Shodmonovna (Zien Journals, 2023)
This article explores the impact of lactose on the human body, focusing on lactose intolerance, a common digestive disorder. Lactose is a natural sugar found in dairy products, and its digestion relies on the enzyme lactase. The keywords for this study include lactose, lactose, lactose intolerance, dairy products, and digestive disorders. The discussion section highlights the significance of this condition and its dietary implications. In conclusion, we provide suggestions for individuals with lactose intolerance and offer insights into potential areas for future research
Keywords: Lactose intolerance; lactase enzyme; digestive system; lactose maldigestion